Assessment of Motor Skills in Children With Visual Impairment: A Systematic and Integrative Review. (May 2019) - Bakke, Hanne Alves; Cavalcante, Wiviane Abreu; Oliveira, Ilana Santos de; Sarinho, Silvia Wanick; Cattuzzo, Maria Teresa
This study aimed to review and examine the tools used to assess psychomotor performance of children with visual impairment. Databases, such as SCOPUS, MEDLINE/PubMed, Medline/EBSCO, Web of Science, LILACS, CINAHL, and ScienceDirect, were searched using Mesh terms. Data from manuscripts fully available in these databases between 1994 and 2017 (except CINAHL—2014) concerning the evaluation, tool development, or intervention for the improvement of motor skills in children (age, 7-10 years) with visual impairment were collected. The Critical Review Form—Quantitative Studies was used to evaluate the quality of the articles. As a result, 1113 articles were found, but only 24 met the inclusion criteria; 66.7% of the articles had moderate quality, with unsatisfactory results regarding the validity and reliability of the tools used to assess these children, as well as the absence of clinical importance and practical application in such studies. Only the Test of Gross Motor Development-2 and Movement Assessment Battery for Children-2 described data on the validation and reliability in visually impaired children. To minimize systematic errors and improve the quality of the investigations, increasing the number of studies regarding the tools, functionality of their activities, and testing the adaptions is necessary.